Eksplorasi Peran Strategis Koder dalam Implementasi Sistem Indonesian Diagnosis Related Groups (iDRG) di Rumah Sakit - Andra Dwitama Hidayat; Nurhadi Nurhadi; Syndia Puspitasari; Adinda Dwi Putri Juniasari (Jurnal Manajemen Informasi dan Administrasi Kesehatan (JMIAK), 2026)
Indonesian Diagnosis Related Groups (iDRG) is an evolution of the INA-CBG system designed to better reflect patient clinical complexity. The case grouping process in iDRG is highly dependent on the accuracy of diagnosis and procedure coding. Previous studies indicate that the accuracy of clinical coding in hospitals in Indonesia remains a significant challenge. This study aims to explore the strategic role of coders in the clinical coding process within the iDRG system in a hospital setting. A qualitative method with a descriptive phenomenological approach was employed, involving in-depth interviews with five informants (four coders and one head of medical records). Data were analyzed using thematic analysis. The results show that coders perceive their role not merely as administrative, but as guardians of clinical and financial data integrity, bridging clinical services and the reimbursement system. Coders demonstrate a good technical understanding of iDRG mechanisms, particularly the impact of clinical data completeness on case grouping. Strategies to maintain accuracy include comprehensive medical record verification, proactive communication with physicians, peer review, and internal audits. Key factors influencing accuracy are the quality of clinical documentation, coder competence, workload, and health information systems. Challenges include non-specific documentation, limited communication with physicians, case complexity, and evolving regulations. This study highlights the importance of a multidisciplinary approach to improve the quality of clinical coding in hospitals.